(untitled) (Mongolian Journal of Agricultural Sciences, 2020)
Sheeppox and goatpox are caused by sheep pox virus (SPPV) and goat pox virus (GTPV), members of Capripoxvirus genus, Poxviridae family. SPPV and GTPV damage host animal’s wool and skin and reduce production of mutton and milk. Because of morbidity and mortality of the diseases, they bring huge economic burden to the country. Main goal was to compare Mongolian sheep pox, goat pox sequences with other strains that were registered in Genebank. In this study, two SPPV and two GTPV field strains from Mongolia and Perego M strain (Biocombinat SOI, Mongolia), Russian and Chinese alive vaccine strains were used. The common DNA extraction method was used and samples were amplified on a nested polymerase chain reaction (nested-PCR) which amplify the full p32 gene of Capripoxvirus. The primers were designed based on the conserved sequences just outside of the p32 gene of SPPV or GTPV. By applying this method to the sheep and goat samples, suspected with SPPV and GTPV infection in Mongolia, the nested-PCR products were obtained from all samples on the predicted size, and the presence of SPPV and GTPV were confirmed via full length sequence analysis of P32 gene. Sequence comparison was performed using the online BLAST program. Sequence identities of nucleotides were analyzed using MUSCLE algorithm. A phylogenetic tree derived from nucleotide sequences was constructed for the Capripoxvirus using the neighbor joining method of MEGA (version X) software. Based on the phylogenetic tree, the Mongolian sheep pox virus, 2017 clustered together with Zabaikalsk strain and Perego strain (Biocombinat SOI, Mongolia). The Mongolian sheep pox virus, 2015 was closer to Tunisian and Chinese Gansu, Shanxi province strains. Chinese vaccine strain AV41, sequenced in this study was clustered with EF522181.1 Chinese Goat pox vaccine strain but Russian sheep pox vaccine strain, sequenced in this study was close to Mongolian goat pox viruses, 2009. The present data provides theoretical references to improve the preventive and control strategy. Based on the phylogenetic tree that we made, we conclude that SPPV and GTPV sequences in Mongolia were closer to Chinese SPPV, GTPV sequences therefore they were most likely imported from China.